2021
DOI: 10.3390/cancers13153689
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Meta-Analysis of Risk Factors for Endometrial Cancer and Development of a Risk Prediction Model Using an Artificial Neural Network Algorithm

Abstract: Objectives: In this study we wished to determine the rank order of risk factors for endometrial cancer and calculate a pooled risk and percentage risk for each factor using a statistical meta-analysis approach. The next step was to design a neural network computer model to predict the overall increase or decreased risk of cancer for individual patients. This would help to determine whether this prediction could be used as a tool to decide if a patient should be considered for testing and to predict diagnosis, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 82 publications
0
8
0
Order By: Relevance
“…A systematic review suggested an increased risk of endometrial hyperplasia with MP containing estrogen plus progestogen therapy (EPT) 4 . A meta-analysis suggested increased risk of endometrial cancer (relative risk [RR], 1.2) with noncontinuous combined EPT (type of progestogen not specified) but not with continuous EPT 10 . Oral MP should be adequately dosed for prevention of endometrial hyperplasia (eg, 200 mg/d for 12-14 d/mo) 11,12 .…”
Section: Formulation Dosing Routes Of Administration and Safetymentioning
confidence: 99%
See 1 more Smart Citation
“…A systematic review suggested an increased risk of endometrial hyperplasia with MP containing estrogen plus progestogen therapy (EPT) 4 . A meta-analysis suggested increased risk of endometrial cancer (relative risk [RR], 1.2) with noncontinuous combined EPT (type of progestogen not specified) but not with continuous EPT 10 . Oral MP should be adequately dosed for prevention of endometrial hyperplasia (eg, 200 mg/d for 12-14 d/mo) 11,12 .…”
Section: Formulation Dosing Routes Of Administration and Safetymentioning
confidence: 99%
“…4 A meta-analysis suggested increased risk of endometrial cancer (relative risk [RR], 1.2) with noncontinuous combined EPT (type of progestogen not specified) but not with continuous EPT. 10 Oral MP should be adequately dosed for prevention of endometrial hyperplasia (eg, 200 mg/d for 12-14 d/mo). 11,12 Off-label use of a levonorgestrelcontaining intrauterine device to prevent endometrial hyperplasia may avoid adverse systemic effects of progestogens and can protect against unwanted pregnancy in women initiating hormone therapy for symptom management before their final menstrual period.…”
Section: Table 1 Frequency Of Adverse Drug Reactionsmentioning
confidence: 99%
“…The findings of the study effectively reduce the amount of unnecessary invasive testing of EC patients. This might be a valuable tool for physicians to utilize in concert with additional indicators to determine whether individuals require enhanced preventative measures before the potential development of EC ( 126 ).…”
Section: Algorithms In Ec Prognosismentioning
confidence: 99%
“…This capability of machine learning algorithms offers a possibility for the investigation and development of risk prediction and diagnostic prediction models in cancer research [36]. It is evident that the use of machine learning methods can improve our understanding of cancer occurrence and progression [35,37]. Thus, developing machine learning-based breast cancer risk prediction models with improved discriminatory power can stratify women into different risk groups, which are useful for guiding the choice for personalized breast cancer screening in order to achieve a good balance in the risk benefit and cost benefit for breast cancer screening.…”
Section: Principal Findingsmentioning
confidence: 99%